2019
DOI: 10.1002/pra2.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a gamified learning platform on elementary school students' flow experiences in leisure reading

Abstract: Reading is the basis of most learning but is regarded by students as a boring activity in Hong Kong. Therefore, schools in Hong Kong have launched different reading programs to promote reading. One of the successful examples is Reading Battle which gamifies the reading comprehension assessments with points, levels, e‐badges and leaderboard on an interactive learning platform. This study looked into how gamification affected the flow experience of students and discussed to what extent the nine flow dimensions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In contrast to Mak et al's (2019) research, their study focused on examining the impact of a gamified learning platform on the flow experiences of elementary school students during leisure reading. The study took place in Hong Kong and employed Reading Battle to enhance students' reading comprehension skills.…”
Section: Findings and Discussion 1 The Game Elements That Can Be Appl...mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to Mak et al's (2019) research, their study focused on examining the impact of a gamified learning platform on the flow experiences of elementary school students during leisure reading. The study took place in Hong Kong and employed Reading Battle to enhance students' reading comprehension skills.…”
Section: Findings and Discussion 1 The Game Elements That Can Be Appl...mentioning
confidence: 99%
“…Many of these dedicated users enjoyed their reading experience so much that they were fully absorbed and oblivious to time constraints and other inconveniences. Mak et al (2019) concluded that the inclusion of these game elements in the platform positively enhanced students' reading experiences and increased their intrinsic motivation levels after participating in the Reading Battle program. Nitiasih & Budiartha (2021) states that gamification encompasses six fundamental features: user, challenge, point, level, badges, and ranking.…”
Section: Findings and Discussion 1 The Game Elements That Can Be Appl...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it is also reported as an effective tool to introduce global perspectives to students beyond the traditional classroom. Previous studies suggested that gamified e-learning platforms are effective in teaching nonsubject knowledge, such as leisure reading (Mak et al, 2019), traffic safety (Riaz et al, 2019), or civic engagement (Hassan, 2017). Not only could the gamified e-learning platform motivate students through the peer-pressure or team collaboration, but it also offers external motivation (i.e., points, achievements, or ranking) that makes students more committed to learning and achieve higher levels of flow experience during the gameplay (Mak et al, 2019).…”
Section: Promoting Global Perspectives Through a Gamified E-learning Platformmentioning
confidence: 99%